Esteroides Anabolizantes como Recurso Ergogênico no Treinamento Físico: Estudo Qualiquantitativo e Experimental - Cruz, Anderson Miguel da (2015)
Regular physical exercise is no longer just leisure option to configure how important adjuvant health strategy. It is inserted in human society since ancient times, linked to war practices, circus, sports and even the survival needs. Nowadays, conducting physical training, especially the force, is part of the practices related to aesthetics, the cult of the body and targeted therapies for body health. For these reasons it is configured as an object of study with singular significance and potential. The combination with pharmacological and nutritional resources may result in the improvement of nosological tables and health upsurge in various situations. Some peculiarities largely fostered by consumer media and the cultural socio make the combination of physical training and use of ergogenic agents hormonal an everyday procedure, for athletes and non-athletes by setting a non-clinical use, classified as self-medication. Objectives: To systematize empirical data related to customs and procederes employed by users of anabolic-androgenic steroids, identify the toxicological composition of the main supplements / drugs found, employed in the fitness area and high sports performance; verify the change in total body mass and bone morphometry of young Wistar rats. Methodology: The study follows a sequential motion in two phases with different dynamics and instruments. Phase I consists of an ethnographic study (quantitative and qualitative) with adults in the city of Goiania, anabolic steroids users, through in-depth interview (recorded) from semi-structured questionnaire (N = 40). Phase II is a biomedical study (toxicology and preclinical). From the pharmacological and supplements / drugs raised in phase I, was made toxicological analysis (HPLC) to identify the chemical composition (Phase IIa), and the systematic use of procedures (structure of courses). The preclinical study designed to investigate the plyometric strength training interaction (in pool with increasing load based on body weight) combined with use of Stanazolol, 0.85 mg / dose. Main results are apresentdos in four articles, 01 with qualiquantitativas features 01 with quantiqualitative profile and 02 with quantitative traits. Most prte of users (75%) admits the use of hormonal anabolic steroids for non-athletes and recognize precisely the potential side effects. Among the most frequently cited drugs, Decadurabolin, Stanazolol and Durateston were the most cited in use alone or in double and triple combinations. The media is seen as highly influential in the choice of the use and trade of ergogenic agents. It featured the use "non-clinical, automedicado" and the practice of polypharmacy. The systematic use is not uniform and displays strong methodological inconsistencies derived from empirical studies conducted by bodybuilding athletes and appropriate inadvertently by the population "non-athlete". The toxicological analysis supplements / medications points out that the composition of the products do not fully contemplate the use of purpose beyond incoherence of the labels, since they do not contain products that hint at the labels and commercial brochures. In preclinical studies (Wistar rat young) there was no significant change in the morphology of the tibia during "one" stanazolol cycle (12 doses). Total body mass showed statistically significant changes for the trained group, trained / medicated and only medicated. Final thoughts: The plyometric strength training (short Abstract xix duration and high intensity), enabled the reduction of total body mass (with and without stanazolol), suggesting that it can be then used in obesity control strategies, enabled a reduction in the index growth of treated animals.